Iconography of the Old Testament Prophets and the Virgin Kyriotissa on the East Wall of the Gračanica Exonarthex - Dimitrijević, Aleksandra R.; Ratković Stevović, Jelena R. (Collection of Papers of the Faculty of Philosophy in Priština, 2023)
The exonarthex of Gračanica has a rich and complex painted programme, which is a testimony to the medieval kingdom of Serbia ruled by the Nemanjić dynasty, after the arrival of the Ottomans in the Serbian regions. This painted programme has been preserved to a certain extent to this day, although the traces of the ravages of time are clearly visible; it is still possible to read and reconstruct the entire thematic programme, as well as to recognise the iconographic and stylistic features of this part of the church. The exonarthex was painted out several times, as it was repeatedly damaged during the turbulent and destructive centuries (14th, 15th, 16th). It was probably fresco painted after its construction (probably around 1330), but there are no physical remains or written sources testifying to this, while today two layers of fresco paintings are clearly visible in the Gračanica exonarthex. The iconography and themes of the younger layer of fresco paintings from 1570 form a more complex and intricate unity in relation to the one that was there originally. The new frescoes have a clear theological background, devotion to the Virgin Mary, who was also the patron of the Gračanica church. The depiction of the cycle of the Virgin celebrates the role of the Virgin in the Incarnation, foretold in prophetic visions. Almost the entire painted programme around the east portal of the Gračanica exonarthex is dedicated to the Mother of God; additionally, some related depictions are shown there, like the Mother of God on the throne with Christ Emmanuel on her lap surrounded by archangels in the lunette above the entrance. The entire composition was introduced with the theme “From above the prophets have prophesied thee”, as shown by the painted busts of six prophets (Isaiah, Solomon, David, Moses, Aaron and Jeremiah) entwined by a decorative vine on the inside of the arch, at the top of which is a waist-high image of Christ giving blessings with both hands. The main aim of this paper is to point out the importance of the restoration and painting of Serbian monasteries during the Ottoman rule since these topics are insufficiently represented in Serbian art history. The paper provides an iconographic analysis of the scenes dedicated to the celebration of the Virgin in the Gračanica exonartex, as well as their theological background.